Socioeconomic determinants of health-care and emotional needs among Iranian older adults in Isfahan - Mehdi Nosratabadi; Seyyed Hamid Nabavi; Vahid Rashedi; Mostafa Amini Rarani (Journal of Education and Health Promotion, 2018)
INTRODUCTION: The main aim of this study was to explore the socioeconomic determinants of health-care and emotional needs among older adults. MATERIALS AND METHODS: In this cross-sectional study, 350 older adults were randomly selected from five geographical regions in Isfahan, 2016. A self-administered checklist was employed to collect health-care and emotional need data among older adults residing day-care centers. Data were analyzed using logistic regression through STATA/SE (version 14). RESULTS: The highest proportion of older adults lived with income 285–855 USD monthly and insured by social security insurance. Illiteracy, loneliness, and low level of income were more prevalent among female older adults than male ones. The emotional needs of single/widow (odds ratio [OR] = 0.299), divorced (OR = 0.133) older people, not having children (OR = 0.811) or grandchildren (OR = 0.684), and illiterates (OR = 0.689) were discovered to be lower than their counterpart groups. As the elderly got older, their health-care needs were met more. Older adults covered by military insurance have their health-care needs met as much as 21% (OR = 1.215) greater than social security insurance. CONCLUSIONS: Regarding health-care needs, economic and monetary factors are still important in meeting this type of needs as well as education and social insurance. While regarding emotional needs, nonmonetary and noneconomic factors, including social network, are important determinants for the satisfaction of emotional needs.